Pyrazolyl coordination polymers of cadmium(II) - da Silva, P. B.; Frem, RCG; Netto, AVG; Mauro, Antonio Eduardo [UNESP]; Ferreira, J. G.; Santos, RHA (Elsevier B.V., 2006)
The coordination polymers [Cd(mu-Cl)(2)(HPz)(2)](n) (1) and [Cd(mu-1,3-SCN)(2)(HPz)(2)](n) (2) (HPz = pyrazole) have been prepared and characterized by elemental analysis, infrared spectroscopy, and single crystal X-ray diffraction. Both complexes exhibited chain structures made by linear arrays of Cd(II) bridged by chloro (1) or inversely related 1,3-SCN groups (2) and the pyrazole ligands at the apical. sites. Intermolecular hydrogen bonds and another non-covalent interactions are responsible for the self-assembly of linear chains into 2D networks. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: coordination polymers; pyrazole; cadmium(II); thiocyanate; non-covalent interactions; self-assembly